The Coronaviruses of Animals and Birds: Their Zoonosis, Vaccines, and Models for SARS-CoV and SARS-CoV2 - Alluwaimi, Ahmed M.; Alshubaith, Ibrahim H.; Al-Ali, Ahmed M.; Abohelaika, Salah (Frontiers in Veterinary Science, 2020)
The viruses of the family Coronaviridae are ubiquitous in nature due to their existence in a wide spectrum of mammals and avian species. The coronaviruses, as RNA viruses, exist as quasispecies because of their high rate of mutations. This review elaborates on the pathogenesis and the developed vaccines of most of the ubiquitous coronavirus' diseases, mainly bovine, dromedary camel, porcine, feline, canine, and avian coronaviruses. The review emphasizes the significant setbacks in the full exploitation of most of the pathogenesis of the coronavirus' diseases, raising the prospect of effective vaccines for these diseases. The therapeutical trials for the treatment of SARS-CoV2 and the setbacks of these trials are also addressed. The review draws attention to the lessons accumulated from the large number of studies of the pathogenesis of animals and birds' coronaviruses and their vaccines, particularly the bovine, feline, and avian coronaviruses. The lessons drawn from the studies will have an immense influence on how the human coronaviruses pathogenesis and vaccine development will proceed. In addition, the extensive efforts to designate suitable animal models to study the lately emerged human coronaviruses are one of the invaluable contributions carried out by veterinarian scientists. Finally, factors and determinants that contribute to the possibility of emerging new coronavirus zoonotic disease are elaborated on and a call goes out to urge transdisciplinary collaboration in the implementation of the “One Health” concept.